2014
DOI: 10.1371/journal.pone.0084671
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Therapeutic Potential of Adipose Stromal Cells in Early Stage Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is the leading cause of blindness in working-age adults. Early stage DR involves inflammation, vascular leakage, apoptosis of vascular cells and neurodegeneration. In this study, we hypothesized that cells derived from the stromal fraction of adipose tissue (ASC) could therapeutically rescue early stage DR features. Streptozotocin (STZ) induced diabetic athymic nude rats received single intravitreal injection of human ASC into one eye and saline into the other eye. Two months post ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 75 publications
(93 reference statements)
7
110
0
Order By: Relevance
“…MSCs could thus have a great impact on DR treatment since they can act as immunomodulatory agents and reactive oxygen species (ROS) scavengers [98]. Furthermore, due to striking similarities between MSCs and pericytes, MSCs might replace the latter, thereby compensating for pericyte loss [99]; Mendel et al, and Rajashekhar et al, have shown that adipose-derived MSCs intravitreally injected into diabetic mice were able to migrate and integrate into the retinal vasculature, leading to microvascular stabilisation and a marked reduction in capillary dropout [100,101].…”
Section: Msc-related Therapy For Diabetic Retinopathymentioning
confidence: 99%
“…MSCs could thus have a great impact on DR treatment since they can act as immunomodulatory agents and reactive oxygen species (ROS) scavengers [98]. Furthermore, due to striking similarities between MSCs and pericytes, MSCs might replace the latter, thereby compensating for pericyte loss [99]; Mendel et al, and Rajashekhar et al, have shown that adipose-derived MSCs intravitreally injected into diabetic mice were able to migrate and integrate into the retinal vasculature, leading to microvascular stabilisation and a marked reduction in capillary dropout [100,101].…”
Section: Msc-related Therapy For Diabetic Retinopathymentioning
confidence: 99%
“…This study demonstrated that the adipose-derived stromal cells can rescue the neural retina from hyperglycemia-induced degeneration, and improved visual function. 19 …”
Section: Mscs For Diabetic Complicationsmentioning
confidence: 99%
“…113 Moreover, ASCs intravitreal inoculation into type I diabetic athymic nude rat led to improvement of electroretinogram, thus also providing neuroprotection. 114 Pluripotent stem cells (PSC) represented until recent discovery of induced PSC (iPSC) mostly by embryonic stem cells (ESC) are able to differentiate into any cell type of all three main lineages. ESC-derived retinal progenitor cells showed their ability to integrate and differentiate into functional photoreceptors, as evidenced by a significant improvement of vision in mouse models of retinal degeneration, 115,116 although it is unclear whether neuroretinal replacement is likely to be successful in diabetes.…”
Section: Asc and Ipscmentioning
confidence: 99%